FORMATION OF COGNITIVE CAPITAL IN THE CONDITIONS OF A MODERNRISK ENVIRONMENT - KOZAK, Kateryna; LAGODIIENKO, Nataliia; RYBALKO, Serhiy; DEMCHENKO, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The paper explores the theoretical and practical aspects of the formation of cognitive capital in a modern risk environment. The essence of cognitive capital as a specific form of human capital is revealed, which includes a set of knowledge, skills, competencies, and abilities of individuals to learn and transform reality. The features of the modern risk environment, characterized by high uncertainty, rapid technological changes, and transformation of socio-economic relations, are analyzed. The key factors influencing the formation of cognitive capital are identified, including digitalization, increasing complexity of economic systems, and increasing uncertainty. Particular attention is paid to developing such components of cognitive capital as adaptive thinking, critical thinking, creativity, and emotional intelligence. The role of educational systems and organizations in forming cognitive capital is investigated, including the transformation of traditional educational models and the development of new forms of learning. The importance of collective cognitive capital and the role of social networks in its formation are considered. The impact of digital technologies and artificial intelligence on the development of cognitive capital is analyzed. The need for a systemic approach to the formation of cognitive capital is substantiated, which considers the relationship between individual and collective development, the role of technologies and social networks, and the importance of formal and informal learning. The role of public policy in creating favorable conditions for the development of cognitive capital and ensuring the coordination of efforts of various stakeholders in this process is determined.